Influence Oil Price towards Macroeconomic Indicators in Russia - Nyangarika, Anthony; Mikhaylov, Alexey; Richter, Ulf Henning (International Journal of Energy Economics and Policy, 2018)
This paper proposes the effect of oil price shocks on the Russian economic indicators using time series for the period 1991-2016 year to cover all of oil price shocks. The vector autoregressive and the Dickey-Fuller test were utilized to investigate the long-run and the short-run relationships between variables. From the results shows that one of the most important external impact factor is the world price of oil. The research suggests a positive and significant long-term relationship between oil prices and Russian GDP dynamics. Keywords: oil price shocks, GDP growth, forecasting, oil impact. JEL Classifications: C51, C58, F31, G12, G15 DOI: https://doi.org/10.32479/ijeep.6807